Status of Indigenous Chicken Rearing in Krishna District of Andhra Pradesh - Nirmala, T. Vijaya; Prasad, Sunitha; Subrahmanyeswari, B.; Kumari , K. Nagaraja (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
Backyard poultry plays an important role in the livelihood of rural families in developing countries as a source of ready cash income alongwith satisfying social needs. This paper is based on a study conducted in eight villages from Nuzvid division of Krishna District of Andhra Pradesh to assess the status of backyard poultry rearing. The survey indicated the existence of desi birds in the study area with an average flock size of 4-9 birds per household with little or negligible supplementary feeding. High mortality, poor productivity was reported by majority of the respondents which might be due to lack of awareness about improved backyard varieties and poultry related government schemes. Appropriate institutional support in terms of provision of improved backyard varieties, disease control strategies, training and awareness programmes can promote this remunerative enterprise in the region keeping in view of raising demand for backyard egg and chicken.
Keywords: Backyard Poultry; Desi Chicken; Egg Production; Economic Status